Why AI undermines democracy and what to do about it - Coeckelbergh, Mark, 1975- (Cambridge ; Hoboken : Polity, 2024)
Why AI Undermines Democracy and What To Do About It Mark Coeckelbergh Across the world, AI is used as a tool for political manipulation and totalitarian repression. Stories about AI are often stories of polarization, discrimination, surveillance, and oppression. Is democracy in danger? And can we do anything about it? In this compelling and balanced book, Mark Coeckelbergh reveals the key risks posed by AI for democracy. He argues that AI, as currently used and developed, undermines fundamental principles on which liberal democracies are founded, such as freedom and equality. How can we make democracy more resilient in the face of AI? And, more positively, what can AI do for democracy? Coeckelbergh advocates not only for more democratic technologies, but also for new political institutions and a renewal of education to ensure that AI promotes, rather than hinders, the common good for the twenty-first century.
Kniha zkoumá, jak rozvoj umělé inteligence ohrožuje základní principy demokracie. Autor se věnuje problémům, jako jsou manipulace veřejného mínění, automatizace rozhodovacích procesů a koncentrace moci v rukou technologických korporací. Publikace nabízí kritický pohled na současné trendy a navrhuje strategie pro ochranu demokratických hodnot v digitálním věku. Je určena odborníkům i širší veřejnosti zajímající se o politiku, etiku a technologie.
Obsahuje bibliografii, bibliografické odkazy a rejstřík
Keywords: umělá inteligence; společenská transformace; demokracie; politické aspekty; filozofické aspekty; filozofie techniky; pojednání; artificial intelligence; social transformation; democracy; political aspects; philosophical aspects; philosophy of technology; essays